PENGARUH TRANSFORMASIONAL LEADERSHIP DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI: Studi Pada Kantor Kecamatan Langgikima Kabupaten Konawe Utara Selatan - Rina; Tasrudin (Perkumpulan Dosen Manajemen Indonesia, 2021)
This research was conducted with the aim of: 1) Analyzing the effect of Transformational Leadership on the performance of Langgikima District Office employees, North Konawe Regency, 2) Analyzing the influence of motivation on the performance of Langgikima District Office employees, North Konawe Regency and 3) Analyzing the effect of Transformational Leadership and Motivation on Office employee performance Langgikima District, North Konawe Regency This study uses primary data and secondary data. The study population was 24 employees of the Langgikima District Office in North Konawe Regency in September 2020. The sample was 24 people’s using the sensus method. Collecting data through: observation, interviews, questionnaires and documentation. The analytical method used is multiple linear regression analysis with the SPSS program version 23. The results of the study prove that simultaneously the variables of Transformational Leadership and Motivation have a positive and significant effect on the performance of the employees of the Langgikima District Office of North Konawe Regency with an F-count 10.084 with sig = 0.05. Partially the motivation variable has a dominant influence compared to other variables with a coefficient of determination (R2) is 0.49.